Service Quality Modeling for Housing Procurement Project by Sharia Construction Management and Green Building Principles - Sedayu, Agung (Proceedings of the International Conference on Green Technology, 2017)
The services quality of housing procurement by contractors and developers creates many problems and conflicts between parties involved in the project. Unsatisfactory work result for user so that need evaluation based on voice of user. This research aims to develop a prediction model of performance and service quality of contractor/developer on housing procurement projects. The review of this research study is based on the principles of sharia construction management and green building. The result obtains 1 dependent variable which is the service quality of house procurement and eight independent variables include Assurance, Responsiveness and Reliability, Performance, Aesthetics, Easiness, Durability, Islamic Design, and Eco-friendly. The analysis result get the influence of eight service variables which represented by value of R Square = 0,984, meaning variation of service quality of house procurement by contractor/developer can be explained by regression equation equal to 98,4% and 1,6% explained by other variables outside from the equation model. Value R of 0.950 means that the influence of the eight service variables is very strong. The model can be used as a tool to predict evaluation performance and service quality of housing procurement projects.